1999
DOI: 10.1155/1999/140498
|View full text |Cite
|
Sign up to set email alerts
|

Four Years Analysis of Cancer Genetic Clinics Activity in France from 1994 to 1997: A Survey on 801 Patients

Abstract: AIM: In order to evaluate the characteristics and the evolution of cancer genetics activity in France, a survey was conducted at the national level during a period of 4 years from 1994 to 1997 through the French Cooperative Network, a multidisciplinary group formed to investigate inherited tumors.METHOD: A questionnaire was sent to all the 29 French non-specialized cancer genetic clinics to evaluate activity during a period of 4 consecutive weeks each year from 1994 to 1997. Items concerning the cancer genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…This study was carried out on a national sample of French families selected throughout the country. In France there exist more than 32 CGC covering the whole country (Sobol et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This study was carried out on a national sample of French families selected throughout the country. In France there exist more than 32 CGC covering the whole country (Sobol et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of cancer genetic services in France and the United Kingdom have shown that there is a large demand for such services, especially in the area of breast cancer genetics. [4][5][6] According to a survey of North American genetic counsellors, cancer genetics is among the top three most commonly cited specialty areas. 7 We estimate that there are approximately 4200 consultations conducted for breastovarian cancer each year in Ontario, or one for every 1400 women in the population.…”
Section: Discussionmentioning
confidence: 99%
“…A finding pointing to the presence of an increased cancer risk goes beyond the consultee's individual body, and means bad news for her entire family. Even when the consultee already suffers from cancer -this is the case in approximately half of the French consultations (Sobol et al, 1999) -the encounter will focus not on her present cancer but on the genetic risk this cancer may express -a risk that she shares with other members of her family, in particular her children. A consultee sitting in a cancer genetic clinic is not, thus, the only patient in the room.…”
Section: Assessing Family Riskmentioning
confidence: 99%